Factors Predicting Reading in Indonesian Adolescents - Arumsari, Chysanti; Jap, Bernard Amadeus Jaya; Tiatri, Sri; Jap, Tjibeng (Makara Human Behavior Studies in Asia, 2019)
The current study investigates predictors of reading abilities of adolescents in Standard Indonesian (SI). Reading predictors typically signify, with some degree of error, essential cognitive skills needed for individuals to read effectively. This is crucial since it forms a key part of the initial steps to assess or identify reading-related language impairments such as dyslexia. In addition to measures of reading itself and nonverbal intelligence, the present research examines six empirically motivated potential predictors of reading and decoding: phonological awareness; phonological short-term memory; verbal and semantic fluency; rapid automated naming (RAN); motor control; familial risk; and, self-reported factors. The results show that RAN is a dominant predictor among the other factors that were considered in adolescent SI speakers. The results also show strong support for the notion that the importance of RAN increases as children age. Moreover, it is consistent with previous studies that have argued that RAN is a vital predictor of reading development in transparent orthographies.